Pembelajaran Inovatif Ipa MI/SD Berorientasi Konstruktivistik (Contextual Teaching And Learning) - Yulia Pramusinta (Universitas Islam Lamongan, 2017)
Abstract: Every science teacher is expected to always learn throughout life, including learning how to teach students science better and more interesting, so that students like learning science and are eager to learn it with pleasure as such a provision of life. One of the efforts to deal with it is by implementing CTL-based science learning innovation. Learning innovation is the implementation of a new idea at the micro level in classroom in order to improve the learning process and outcomes. This new idea could be implemented by both adopting and adapting what is already emerging or creating a new way of teaching students. Teachers change their role. They no longer teach, but also facilitate their students in experiencing the learning process. The teachers act as models by modeling how to enthusiastically deal with the lifelong learning, creating conducive conditions so that students could experience the so-called active, creative, effective, and fun (PAKEM) learning. Teachers are also expected to develop the character of their students. There are various learning innovations that could be used by teachers, one of which is primarily based on CTL, which has such characteristics as modeling, constructivism, questioning, developing interpersonal skills, shaping learning communities, reflections, and authentic assessment.Keywords: Science learning, contextual teaching and learning